Rare papillary renal neoplasm with reverse polarity: A case report and review of the literature - Tu, Xi; Zhuang, Xiyao; Chen, Qiong; Wang, Wei; Huang, Chaoyou (Frontiers in Oncology, 2023)
Papillary renal neoplasm with reverse polarity (PRNRP) is an extremely rare renal tumour and was newly named in 2019. This study reported a case of a 30-year-old female patient with a left renal tumour without any clinical symptoms and whose CT scan of her left kidney showed a mass of 2.6 cm×2.3 cm, which was considered to be renal clear cell carcinoma. Laparoscopic partial nephrectomy was performed, and histopathology and immunohistochemistry confirmed papillary renal neoplasm with reverse polarity, which had unique clinicopathological features, immunophenotype, KRAS gene mutation and relatively indolent biological behaviour. As newly diagnosed cases, rigorous and regular follow-up is necessary. In addition, a literature review was performed from 1978 to 2022, and 97 cases of papillary renal neoplasms with reverse polarity were identified and analysed.